Perencanaan Produksi Agregat CV XYZ Dengan Jumlah Tenaga Kerja Tetap: Aggregate Production Planning CV XYZ with Amount of Permanent Employment - Fadhillah Fairuzzahira; Sukardi Sukardi; Yandra Arkeman (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
CV XYZ is a growing plywood company. In increasing the company's competitiveness, CV XYZ seeks to find more ideal production planning for the company. The difference between supply and demand of CV XYZ has a total gap of 7,676 m3 over a period of 30 months. This proves that the current CV XYZ production planning is not ideal to be able to keep up with fluctuating demand. This study aims to analyze medium term production planning. Demand forecasting method is used to determine demand in the coming 12 months period. To compare the current CV XYZ strategy with the level, chase, mixed strategy. Based on calculations that have been made using demand and CV XYZ production variables, it is known that the ideal method used for future production planning is the chase strategy. The chase strategy focuses on eliminating existing inventory in the company, using adjusting the number of working days to the number of demands, as well as purchasing units from subcontracts. The use of a chase strategy has a 43% lower cost impact. In 2017-2018, the average monthly production cost is Rp1,633,316,531 to Rp930,905,200. Keywords: demand forecasting, aggregate planning, level strategy, chase strategy, mixed strategy